Interface Engineering in Perylene Diimide-Based Organic Photovoltaics with Enhanced Photovoltage - Mohapatra, Aiswarya Abhisek; Pranav, Manasi; Yadav, Suraj; Gangadharappa, Chandrasekhar; Wu, Jiaying; Labanti, Chiara; Wolansky, Jakob; Benduhn, Johannes; Kim, Ji-Seon; Durrant, James; Patil, Satish (ACS applied materials & interfaces, 2023)
The introduction of nonfullerene acceptors (NFA) facilitated the realization of high-efficiency organic solar cells (OSCs); however, OSCs suffer from relatively large losses in open-circuit voltage (V OC) as compared to inorganic or perovskite solar cells. Further enhancement in power conversion efficiency requires an increase in V OC. In this work, we take advantage of the high dipole moment of twisted perylene-diimide (TPDI) as a nonfullerene acceptor (NFA) to enhance the V OC of OSCs. In multiple bulk heterojunction solar cells incorporating TPDI with three polymer donors (PTB7-Th, PM6 and PBDB-T), we observed a V OC enhancement by modifying the cathode with a polyethylenimine (PEIE) interlayer. We show that the dipolar interaction between the TPDI NFA and PEIEenhanced by the general tendency of TPDI to form J-aggregatesplays a crucial role in reducing nonradiative voltage losses under a constant radiative limit of V OC. This is aided by comparative studies with PM6:Y6 bulk heterojunction solar cells. We hypothesize that incorporating NFAs with significant dipole moments is a feasible approach to improving the V OC of OSCs.